New Approaches to Wipe Sampling Methods for Antineoplastic and Other Hazardous Drugs in Healthcare Settings - Connor Thomas H.; Smith Jerome P. (De Gruyter, 2016)
Purpose: At the present time, the method of choice to determine surface contamination of the workplace with antineoplastic and other hazardous drugs is surface wipe sampling and subsequent sample analysis with various analytical techniques. The purpose of this article is to review current methodology for determining the level of surface contamination with hazardous drugs in healthcare settings and to discuss recent advances in this area. In addition it will provide some guidance for conducting surface wipe sampling and sample analysis for these drugs in healthcare settings.